1997
DOI: 10.1093/ajcn/66.1.52
|View full text |Cite
|
Sign up to set email alerts
|

beta-Carotene in breast milk and serum is increased after a single beta-carotene dose

Abstract: Normal lactating mothers were administered a single dose of 60 or 210 mg beta-carotene and changes in serum and milk retinol, alpha-tocopherol, and carotenoids were monitored for 8 d. Average serum beta-carotene concentrations increased 4.1- and 4.0-fold after the 60- and 210-mg doses, respectively. Milk beta-carotene concentrations increased 4.1- and 3.0-fold after the 60- and 210-mg doses, respectively. Maximum serum concentrations were reached 24 h after both supplements, although concentrations of milk bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
2
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 36 publications
9
37
2
2
Order By: Relevance
“…A similarly high correlation has already been reported by other authors (29,30) , although weaker correlations have also been described in the literature (11) . Breast milk lutein concentration in our study was equal to approximately 40 % of the plasma value, data that are supported by other studies (12,31) .…”
Section: Discussionsupporting
confidence: 93%
“…A similarly high correlation has already been reported by other authors (29,30) , although weaker correlations have also been described in the literature (11) . Breast milk lutein concentration in our study was equal to approximately 40 % of the plasma value, data that are supported by other studies (12,31) .…”
Section: Discussionsupporting
confidence: 93%
“…The circulating lutein zeaxanthin level in this Nepali population was similar (Ribaya-Mercado et al, 1995;Rock et al, 1995) or higher (Ascherio et al, 1992;Forman et al, 1996;Can®eld et al, 1997Can®eld et al, ,1998Mayne et al, 1998) than reported among American adults. This comparability, between a markedly malnourished population in Nepal and wellnourished groups in the United States, is unexplainable.…”
Section: Discussionsupporting
confidence: 80%
“…The level of circulating b-carotene in our population was much lower than distributions reported in the well-nourished lactating (Can®eld et al, 1997(Can®eld et al, ,1998 or non-lactating women (Forman et al, 1996;Rock et al, 1995). This may Retinol, tocopherol and carotenoid in Nepali women S Yamini et al not be surprising among controls, given the low intakes of vegetables, fruit and dietary fat (data not shown) that might be expected to enhance carotenoid absorption (Takyi, 1999).…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations